2006
DOI: 10.1111/j.1365-3059.2006.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

First report of Penicillium allii as a field pathogen of garlic (Allium sativum)

Abstract: Blue mould disease in garlic ( Allium sativum ) is associated worldwide with various Penicillium species, and has been attributed to significant annual crop losses in Argentina; the world's second largest exporter of garlic. To identify the pathogenic Penicillium species responsible, affected plants were sampled in La Consulta station (33 ° 45 ′ S, 69 ° 02 ′ W) and placed in a damp chamber. Characteristic disease symptoms are stunted and chlorotic plants with withered leaves and reduced bulb size. Bulbs are of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…(2005) found that amongst several isolates in their collection, only those identified as Penicillium allii Vincent & Pitt were strongly pathogenic to garlic, and that isolates bearing the name P. hirsutum were not very aggressive. Valdez et al. (2006) thought the name P. allii preferable to P. hirsutum for those isolates pathogenic to garlic in Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…(2005) found that amongst several isolates in their collection, only those identified as Penicillium allii Vincent & Pitt were strongly pathogenic to garlic, and that isolates bearing the name P. hirsutum were not very aggressive. Valdez et al. (2006) thought the name P. allii preferable to P. hirsutum for those isolates pathogenic to garlic in Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…However, since then P. corymbiferum has been subdivided into several different species contained within the Penicillium series Corymbifera (with synonymy of the original P. corymbiferum characterization aligned with that of P. hirsutum ). In Argentina, P. viridicatum (Gatica & Oriolani, 1984), P. hirsutum (Cavagnaro et al ., 2005) and P. allii (Valdez et al ., 2006) have all been reported as garlic pathogens. Penicillium viridicatum has also been reported from garlic in Japan (Saito & Tsuruta, 1984) and Poland (Machowicz‐Stefaniak et al ., 1998), although in the Polish study pathogenicity of the isolates was not confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Penicillium viridicatum has also been reported from garlic in Japan (Saito & Tsuruta, 1984) and Poland (Machowicz‐Stefaniak et al ., 1998), although in the Polish study pathogenicity of the isolates was not confirmed. Recently, doubt has been raised regarding the correct taxonomic identification of the reported P. viridicatum causal agents, as the P. viridicatum strains ATCC 9635 (Smalley & Hansen, 1962), IFO 7736 = CBS 390·48 ex‐type (Saito & Tsuruta, 1984), IBT 15053 = CBS 101034 and IBT 16639 (Valdez et al ., 2006) failed to establish a colony or to sporulate on infected garlic bulbils in damp chambers. As P. allii and P. viridicatum are macro‐ and micromorphologically quite similar, it is possible that the P. viridicatum isolates previously reported as causal agents were in fact P. allii .…”
Section: Introductionmentioning
confidence: 99%
“…genera Chromocleista and Penicillium of the class Eurotiomycetes were higher in the Dongdo sample than in the Ulleungdo and Seodo samples. The genus Penicillium comprises saprophytic, pathogenic, and/or endophytic fungi (da Costa et al, 1998;Khan et al, 2008;Samson et al, 2004;Valdez et al, 2006). Interestingly, the genus Gibberella of the class Sordariomycetes was only detected in the Dongdo and Seodo samples.…”
Section: Archaeorhizomycetesmentioning
confidence: 99%
“…The family Herpotrichiellaceae of the class Eurotiomycetes of Ascomycota was present at high levels only in the Dongdo sample, whereas the family Trichocomaceae comprised greater than 1.0% of all families detected in the Dongdo and Seodo samples. Members of Herpotrichiellaceae have been characterized as human pathogens (de Hoog et al, 2003;Haase et al, 1999), while members of Trichocomaceae maintain saprophytic, pathogenic, and/or endophytic characteristics (da Costa et al, 1998;Khan et al, 2008;Samson et al, 2004;Valdez et al, 2006). The families Clavicipitaceae and Hypocreaceae of the class Sordariomycetes of Ascomycota were slightly more abundant in the Dongdo sample than in the Ulleungdo Fungal classes with a relative abundance greater than 1% in at least one of the three samples are shown.…”
Section: Archaeorhizomycetesmentioning
confidence: 99%